The Role of Pathway to English in Reducing Teacher Burnout in English Language Teaching - Ulya, Lina; Pitria, Ainul; Maulana, Arief Ginanzar (UICELE, 2026)
Teacher burnout has become an important issue in English Language Teaching (ELT), particularly due to increasing instructional demands and workload. One factor that may help teachers manage these challenges is the availability of well-structured teaching materials. This study aims to explore the role of Pathway to English, published by Erlangga, in supporting English teachers’ instructional practices in ELT classrooms. This study employed a qualitative descriptive method using a questionnaire administered to English teachers who use Pathway to English Phase F in their teaching practice. The findings indicate that the textbook supports teachers by providing well-structured lesson organization, ready-to-use learning activities, contextually relevant materials, and integrated language exercises. These features help reduce instructional preparation time and facilitate classroom management while supporting the implementation of the Learning Outcomes (Capaian Pembelajaran/CP) of Phase F in the Merdeka Curriculum. Rather than directly demonstrating a reduction in teacher burnout, the findings suggest that Pathway to English serves as an instructional resource that helps lessen teachers’ workload and provides pedagogical support. Such support may contribute to more manageable teaching practices and may help address factors associated with teacher burnout. Further studies employing validated burnout measurement instruments are recommended to examine this relationship more directly.